2004
DOI: 10.1111/j.1523-1755.2004.00871.x
|View full text |Cite
|
Sign up to set email alerts
|

Duffy antigen receptor and genetic susceptibility of African Americans to acute rejection and delayed function

Abstract: The susceptibility of African American recipients to acute rejection and to DGF was not confirmed to be associated with DARC alleles or genotype. Future studies should exclude a potential role of donor-related DARC in transplant outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
(26 reference statements)
1
10
0
1
Order By: Relevance
“…They found that the Duffy-negative phenotype was commonly associated with rejection in the setting of delayed graft function, but there was no correlation with outcome beyond this subset. A later study confirmed no association between any Duffy phenotypes and acute rejection, or delayed graft function [18]. These studies were both small, and although they were looking for a large difference in outcomes, they may have been insufficiently powered to detect any significance.…”
Section: Darc and Transplantationmentioning
confidence: 94%
“…They found that the Duffy-negative phenotype was commonly associated with rejection in the setting of delayed graft function, but there was no correlation with outcome beyond this subset. A later study confirmed no association between any Duffy phenotypes and acute rejection, or delayed graft function [18]. These studies were both small, and although they were looking for a large difference in outcomes, they may have been insufficiently powered to detect any significance.…”
Section: Darc and Transplantationmentioning
confidence: 94%
“…Similarly, Mange et al were not able to demonstrate an association between recipient-related allelic variants of the DARC gene and acute rejection among 181 African-American recipients of cadaveric renal allografts [88].…”
Section: Reviewmentioning
confidence: 97%
“…Although this difference is multifactorial, African-Americans apparently have heightened immune reactivity with increased numbers of activated T cells, blastogenesis and increased costimulatory responses [39,40]. In addition, Lewis and Duffy red cell antigen receptor differences in African-Americans compared with whites have also been implicated as playing a role in the increased immunogenicity of African-Americans [41,42]. These blood type differences may explain the fact that, in comparison to whites, African-Americans experience a 1.5-year longer waiting time for deceased donors [16], and waiting time is known to negatively impact graft survival results [43].…”
Section: Recipient Racementioning
confidence: 99%